What's next for size-sound symbolism? - Ekström, Axel G. (Frontiers in Language Sciences, 2022)
This text reviews recent research in phonetic size-sound symbolism – non-arbitrary attributions of size properties to speech acoustic properties. Evidence from a wide range of research works is surveyed, and recent findings from research on the relationships between fundamental frequency, vowel articulation, consonant articulation, phonation type, mora count, and phonemic position, are discussed. It is argued that a satisfactory explanatory model of phonetic size-sound symbolism should meet two criteria: they should be able to explain both (1) the relationship between size and speech acoustics (Association criterion), and (2) the inconsistent findings observed across languages in the relevant literature (the Inconsistency criterion). Five theories are briefly discussed: The frequency code, Embodied cognition, Sound-meaning bootstrapping, Sapir-Whorf hypotheses, and Stochastic drift. It is contended that no currently available explanatory model of size-sound symbolism adequately meets both criteria (1) and (2), but that a combination of perspectives may provide much of the necessary depth. Future directions are also discussed.